ISOLATION AND IDENTIFICATION OF PROMISING AMMONIFYING AND NITRIFYING BACTERIA FROM AGRICULTURAL FIELDS OF VISAKHAPATNAM - SUJATHA PEELA; DEEPIKA DIVYA KADIRI; NARESH GORLE; KRISHNAKANTH VARADA RAJU PEETALA (International Journal of Pharma and Bio Sciences, 2015)
Microorganisms are indispensable components of our ecosystem. Soil microorganisms, such as bacteria and fungi, play key roles in soil fertility and promoting plant health. The improvement of soil fertility is one of the most common strategies to increase agricultural production by maintaining high levels of available nitrogen (N) and phosphorus (P), the two most limiting nutrients in soil. The objective of the present study is to isolate and identify promising ammonifying and nitrifying bacteria from soil samples collected from 12 different agricultural fields of Visakhapatnam. Bacteria with predominant morphological types were selected randomly from agar plates and isolated on minimal medium i.e. Yeast Extract Mannitol agar, Ashby’s Mannitol Agar media for ammonifying and nitrifying bacteria. The bacterial isolates were identified using Bergey’s manual of bacteriology. The bacterial isolates Pseudomonas, Bacillus, Proteus, Enterobacter, Klebsiella, were identified as ammonifying bacteria and Azotobacter, Nitrobacter, Nitrococcus, Nitrosomonas, were identified as nitrifying bacteria in the agricultural fields. Then the soil samples were tested for the presence of Ammonia, Nitrite and Nitrate by incubating the soil samples for a week in Ammonifying, Nitrite and Nitrate forming broths respectively. Based on the color developed the concentration of ammonia, nitrite, and nitrates were detected using spectrophotometer. The amount of organic nitrogen present in the broth was estimated by neutralization method using Nessler’s reagent. Our work suggests that these ammonifying and nitrifying bacteria isolated from the agricultural fields were found to be promising and use of these bacteria as bio fertilizers in soils would increase the level of available nitrogen contributing substantially to improve the implantation and development of crops in various regions.